One dimensional steepening of waves in non-ideal relaxing gas. (December 2015) - Singh, Randheer; Jena, J.
Abstract: In this paper, we studied the behavior of different modes of wave propagation and breaking of wave front by employing the theory of singular surfaces in a plane and radially symmetric flow of a non-ideal relaxing gas. The one dimensional steepening of waves is considered and the transport equation for the jump discontinuity of velocity gradient is obtained. The effects of relaxation and van der Waals excluded volume of the medium on the jump discontinuity of velocity gradient are analyzed. Abstract : Highlights: Behavior of steepening of waves in a non-ideal relaxing gas is investigated. Relations between the jumps in the gradient of flow parameters are established. Observed that the jump in velocity gradient satisfies a Bernoulli type of equation. Effects of relaxation & non-ideal parameter on jump in velocity gradient are studied.